2014
DOI: 10.1074/jbc.m114.569020
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinases, TYRO3, AXL, and MER, Demonstrate Distinct Patterns and Complex Regulation of Ligand-induced Activation

Abstract: Background:The mechanisms by which ligands activate TAM receptors (TYRO3, AXL, and MER) are not well understood. Results:We created a series of TAM reporter cell lines and interrogated ligand-inducible TAM activation. Conclusion: TAMs are differentially activated by GAS6 and protein S and have distinct requirements for phosphatidylserine. Significance: Results reveal molecular mechanisms and rationale for non-overlapping functions of TAMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(215 citation statements)
references
References 56 publications
7
206
0
2
Order By: Relevance
“…However, the related TAM ligand PROS1 preferentially bound sTYRO3 and had much weaker binding to sAXL and sMERTK (Fig. 6C), in agreement with observations by Tsou et al (68) that PROS1 preferentially activates TYRO-3 and GAS6 favors AXL over the other TAM members. When testing the ability of soluble receptors to inhibit MERTK activation, we found that at the concentration of 0.1 M, sAXL effectively inhibited GAS6-induced MERTK phosphorylation while sMERTK could not (Fig.…”
Section: Resultssupporting
confidence: 81%
“…However, the related TAM ligand PROS1 preferentially bound sTYRO3 and had much weaker binding to sAXL and sMERTK (Fig. 6C), in agreement with observations by Tsou et al (68) that PROS1 preferentially activates TYRO-3 and GAS6 favors AXL over the other TAM members. When testing the ability of soluble receptors to inhibit MERTK activation, we found that at the concentration of 0.1 M, sAXL effectively inhibited GAS6-induced MERTK phosphorylation while sMERTK could not (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Merdependent intrinsic chemoresistance 12 may be fundamentally different from coculture-driven Mer upregulation as the formation of complexes between TAM receptor ligands with apoptotic cells can cause an enhancement of Mer signaling. 33 Moreover, it has been shown that Mer is important for the ingestion of apoptotic cells by macrophages, partly by release of Gas6 and perpetuation of Mer activity. 41,42 This "niche"-dependent modulation of Mer may explain why Mer knockdown can result in MTX sensitization, 12 whereas in CNS cocultures, Mer inhibition reverses chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…on May 9, 2018. by guest www.bloodjournal.org From thereby enhancing receptor activation. 33 We therefore measured apoptotic cells in cocultures with leukemic cells and U343 or MSCs. For all cell lines, the number of apoptotic cells was higher in U343 than in MSC cocultures (supplemental Figure 2B).…”
mentioning
confidence: 99%
“…Macrophages were treated with 10 nM γ-carboxylated Gas6 for 1 h, which was added as conditioned medium harvested from Gas6-transfected HEK293-6E cells, as described (53). Conditioned medium from nontransfected HEK293 cells served as the control and is referred to in the figures as "vehicle."…”
Section: Methodsmentioning
confidence: 99%